2006
DOI: 10.1007/s11664-006-0189-7
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, solderability, and growth of intermetallic compounds of Sn-Ag-Cu-RE lead-free solder alloys

Abstract: The near-eutectic Sn-3.5 wt.% Ag-0.7 wt.% Cu (Sn-3.5Ag-0.7Cu) alloy was doped with rare earth (RE) elements of primarily Ce and La of 0.05-0.25 wt.% to form Sn-3.5Ag-0.7Cu-xRE solder alloys. The aim of this research was to investigate the effect of the addition of RE elements on the microstructure and solderability of this alloy. Sn-3.5Ag-0.7Cu-xRE solders were soldered on copper coupons. The thickness of the intermetallic layer (IML) formed between the solder and Cu substrate just after soldering, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 7 publications
2
57
0
Order By: Relevance
“…2: 5). Figure 2 shows the drawing of the measuring platform for potentiodynamic polarisation test, where the counter electrode is platinum (1), working electrode is the cylinder shaped sample made by lead-free solder alloy (2), and a saturated calomel electrode as a reference electrode (4) with Luggin capillary bridge (3) connected to the test medium, which is 3.5 wt.% NaCl solution (6). The active area of the working electrode was about 100 mm 2 .…”
Section: Polarization Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…2: 5). Figure 2 shows the drawing of the measuring platform for potentiodynamic polarisation test, where the counter electrode is platinum (1), working electrode is the cylinder shaped sample made by lead-free solder alloy (2), and a saturated calomel electrode as a reference electrode (4) with Luggin capillary bridge (3) connected to the test medium, which is 3.5 wt.% NaCl solution (6). The active area of the working electrode was about 100 mm 2 .…”
Section: Polarization Testsmentioning
confidence: 99%
“…While, the different qualifying studies of the Pb-free solder alloys are even active topics [3] and one of the issues is carry about humidity induced failures, like electrochemical corrosion [4,5]. Different results were also published related to novel Pb-free solder alloys in terms of reliability topics, such as solderability [6], intermetallic layer (IML) investigation [7], shear force tests [8], wetting investigations [9] or (solid state physics) migration tests [10]. On the other hand, the investigations of humidity induced failures (like corrosion) of Pb-free solder alloys are not deeply addressed in the scientific publications.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] For example, Choi et al 10 investigated the effect of the addition of In on binary eutectic Sn-3.5mass%Ag solder. They reported that microstructure of the solder and the morphology of secondary phases in the solder matrix changed accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the growth thickness of the interfacial intermetallic layers and the consumption of the Ni surface-finished layer on the Cu pads in Sn-3.0Ag-0.5Cu-0.06Ni-0.01Ge solder joints are both slightly less than those in Sn-3.0Ag-0.5Cu. Concerning the addition of rare earth (RE) elements such as La and Ce into the Sn-3.5Ag-0.7Cu solder, Law et al 15 showed that the addition of RE elements improved the wetting behavior of the solder and that intermetallic compound growth was inhibited by adding RE into the solder. Kao et al 16 investigated the effect of the addition of nanosized Cu 6 Sn 5 particles on the interfacial reaction of the solder and Ni-P layer.…”
Section: Introductionmentioning
confidence: 99%
“…Many other researchers have shown that the addition of RE metals improves the mechanical properties of Pb-free solder systems by causing a grain refinement effect and more uniform distribution of the intermetallic compounds (IMCs) within the solder matrix. [5][6][7] In addition, it has been shown that RE dopants reduce the thickness of the IMC interfacial layer in solder joints 8,9 and yield notable improvements in the hardness, tensile strength, shear strength, thermal fatigue, and creep resistance of a wide variety of Pb-free solders. 7,[10][11][12] Although recent work has highlighted quite a few advantages to adding RE elements into solders, the theoretical background of such work remains unclear.…”
Section: Introductionmentioning
confidence: 99%